2011
DOI: 10.1124/mol.111.072405
|View full text |Cite
|
Sign up to set email alerts
|

Heteropoda Toxin 2 Interaction with Kv4.3 and Kv4.1 Reveals Differences in Gating Modification

Abstract: Kv4 (Shal) potassium channels are responsible for the transient outward K ϩ currents in mammalian hearts and central nervous systems. Heteropoda toxin 2 (HpTx2) is an inhibitor cysteine knot peptide toxin specific for Kv4 channels that inhibits gating of Kv4.3 in the voltage-dependent manner typical for this type of toxin. HpTx2 interacts with four independent binding sites containing two conserved hydrophobic amino acids in the S3b transmembrane segments of Kv4.3 and the closely related Kv4.1. Despite these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The inhibition of the Kv4.3 current by the toxin seemed to include both inhibitory mechanisms. A similar voltage-dependent and -independent blockade of Kv4.x currents has been reported recently with heteropoda toxin 2 (Desimone et al 2011). Similar to this report, we found that four amino acids at the end of S3 primarily determine voltage dependence of the toxin action.…”
Section: Voltage-dependent and -Independent Inhibition Of Kv4 Channelmentioning
confidence: 57%
“…The inhibition of the Kv4.3 current by the toxin seemed to include both inhibitory mechanisms. A similar voltage-dependent and -independent blockade of Kv4.x currents has been reported recently with heteropoda toxin 2 (Desimone et al 2011). Similar to this report, we found that four amino acids at the end of S3 primarily determine voltage dependence of the toxin action.…”
Section: Voltage-dependent and -Independent Inhibition Of Kv4 Channelmentioning
confidence: 57%
“…Based on these findings, it would be of considerable interest to know what the tarantula toxins do to voltage sensor inactivation? As to that, it has been found that the toxins more specific for Kv4 channels, including Heteropoda toxins, cause a slowing of macroscopic inactivation, an acceleration of recovery from inactivation and a shift of steady-state inactivation curves to more positive potentials (Sanguinetti et al, 1997; Diochot et al, 1999; Escoubas et al, 2002; Ebbinghaus et al, 2004; DeSimone et al, 2009, 2011). These findings are in accordance with a prevention of the relaxed conformation of the voltage sensor because it is stabilized in its resting conformation.…”
Section: “Intoxication” Of Voltage Sensor Inactivationmentioning
confidence: 98%
“…I to,f recovers from inactivation in the order of milliseconds, whereas I to,s recovers much slower. In order to inhibit I to,f , an inactivating pre-pulse to −40 mV for 50 ms can be applied, which captures I to,f in a closed state (Brouillette et al, 2004); alternatively Heteropoda toxin can be used, which selectively blocks K V 4 channels in low-micromolar concentrations (Sanguinetti et al, 1997; DeSimone et al, 2011; Liu et al, 2011). For evaluating I K,slow1 , the sensitivity toward 4-aminopyridine can be exploited, because I K,slow1 is sensitive in the micromolar range while I to,f , I to,s , and I K,slow2 are sensitive in the millimolar range (Guo et al, 1999).…”
Section: Kchip2 and Ion Channelsmentioning
confidence: 99%